Hubungan Kemampuan Berbahasa Arab Dengan Kemampuan Menghafal Al-Qur’an Siswa Kelas Vlll Smpi Al-Mansyuriyah - Maulida, Riska Amalia; Sahlani, Sahlani; Hakim, Lukmanul (Masterpiece: Journal of Islamic Studies and Social Sciences, 2023)
The ability to speak Arabic is an important aspect of learning Arabic, where Arabic is the language of choice in writing the Qur'an so that as Muslims, especially students, they must have Arabic language skills in order to be able to read the Koran properly and correctly. Therefore, this research aims to determine whether or not there is a relationship between the ability to speak Arabic and the ability to memorize the Al-Quran. This research is a research with a quantitative correlation approach. The population in this study were all students of SMPI Al-Mansyuriyah and the sample in this study was students of class VII at SMPI Al-Mansyuriyah and the sample was determined using probability sampling. Data collection techniques in this study used description tests, interviews and documentation. While the data analysis techniques used descriptive statistical analysis and inferential statistical analysis with the help of SPSS version 23 software using the product moment correlation test. Based on data analysis from the correlation test, the correlation coefficient value is r = 0.981 (ρ = 0.000, ρ <0.005) which means that there is a positive relationship between Arabic language skills and the ability to memorize the Qur'an for fifth grade students at SMPI Al-Mansyuriyah.